Effects of different environmental pollutants on the anatomical features of roadside plants (Progressive Agriculture, 2020)
Experiments were conducted in order to investigate anatomical changes in leaves and stems of roadsides plants namely Mango (Mangifera indica), SilKoroi (Albizia procera) and Mahagony (Sweatenia mahogany). Plants that grown nearby roadside areas were exposed to various kinds of pollutants. To carry out the experiment, samples (Fresh leaves and Stems) were collected from two polluted sites and one control site. For anatomical study leaves and stems were cut into sections in the laboratory and changes were identified under the light microscopy. Results revealed that leaves of selected roadside plants had reduced cell size with black dot like substance deposited in the epidermis, palisade and spongy parenchyma in the polluted sites. But leaves of control site plants had normal anatomy. Meanwhile stem showed changes in vascular bundle of pollution affected sites but no change was found in control site. These results highlighted the importance of anatomical data for precious diagnosis of injury and to determine the sensitivity of roadside plants to different environmental pollutants.Progressive Agriculture 30 (4): 344-351, 2019